Eyelash Trichomegaly: Unusual Feature Associated with Systemic Lupus Erythematosus Patient - Amjad M. AlWarawreh; Ahmad M. AlWarawreh; Bashar F. Jarrar; Asem H. Aldebei; Mahasen S. Ajarmeh; Fadi F. Ayyash; Manal A. Abu Al-Ghanam (Case Reports in Medicine)
Eyelash trichomegaly is a rare disorder in which normal features of eyelashes such as length, color, thickness, or curling changes. It may occur due to many causes, such as the presence of other disorders such as HIV infection, congenital anomalies like oculocutaneous albinism, or Oliver–McFarlane syndrome. It may be linked to the use of certain drugs and can also be present as an isolated trait by birth. Here, we report a rare case of eyelash trichomegaly in a 19-year-old female having diffused alopecia, diagnosed with systemic lupus erythematosus.